Junie B. Jones and some sneaky peeky spying - Park, Barbara; Brunkus, Denise (New York : Scholastic, 1994)
Six-year-old Junie B.'s penchant for spying on people and her curiosity about the private life of her teacher get her in trouble at kindergarten.
K
Series title and number from v. 5.
"A First stepping stone book."
b
b
Keywords: Kindergarten -- Fiction; Schools -- Fiction; Teachers -- Fiction; Humorous stories